Comparative analysis of the effects of institutional factors and Piketty's Hypothesis on inequality: Evidence from a panel of countries - Ali Sarkhosh-Sara; Khadije Nasrollahi; Karim Azarbayjani; Rasul Bakhshi Dastjerdi (Journal of Economic Structures, 2020)
There are many reports on investigating the influences of institutional factors and Piketty's Hypothesis on income inequality; nonetheless, the inequality effects of both factors are seemingly investigated separately. We hypothesize that economic freedom viewed as an institutional improvement or distortion has comparatively larger effects on inequality than the forces of income divergence introduced by Thomas Piketty. This article revisits the income inequality-(r-g) nexus and uncovers the role of economic freedom as an institutional indicator in explaining the relationship. Considering the latest inequality data of World Inequality Database (WID) and Standardized World Income Inequality (SWIID) for 82 countries over 2000-2017, an inequality model is estimated that explicitly captures the interaction effect of (r-g) and economic freedom. Reaffirming that economic freedom affects inequality in a non-linear form, we also found evidence that (r-g) raises inequality in the short run, demonstrating that preexisting holders of capital derive greater shares of income. Nevertheless, the effect of (r-g) is not as strong as that of economic freedom and is insignificant in highly unequal countries. This implies that institutional factors play a more important role than Piketty's Hypothesis in the presence of high inequality. Furthermore, variables of inflation, gross savings rate, trade openness, and unemployment rate are shown to be the most consistently positive and significant factor and GDP per capita, government spending, natural resource rent, and tax revenue variables have negative and significant effects on the baseline estimations.
Keywords: 330; Economic freedom; (r-g); Income inequality; Piketty